0,3x-2(0,1x+1)=0
0,5(x-3)+0,25(2x+6)=5
0,3x - 2(0,1x+1) = 0
0,3x - 0,2x - 2 = 0
0,1x - 2 = 0
0,1x = 0+2
0,1x = 2
x = 2 : 0,1
x = 20
0,5(x-3) + 0,25(2x+6) = 5
0,5x - 1,5 + 0,5x + 1,5 = 5
1x = 5
x = 5 : 1
x = 5
Pozdrawiam :)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
0,3x - 2(0,1x+1) = 0
0,3x - 0,2x - 2 = 0
0,1x - 2 = 0
0,1x = 0+2
0,1x = 2
x = 2 : 0,1
x = 20
0,5(x-3) + 0,25(2x+6) = 5
0,5x - 1,5 + 0,5x + 1,5 = 5
1x = 5
x = 5 : 1
x = 5
Pozdrawiam :)